2021
DOI: 10.1002/imhj.21918
|View full text |Cite
|
Sign up to set email alerts
|

Maternal lack of sleep in the first two years after childbirth: Perceived impacts and help‐seeking behaviors

Abstract: Most evidence‐based sleep interventions (e.g., graduated extinction of nighttime crying) are in opposition to many parents’ values. This warrants taking a step back and asking the parents about their main concerns regarding their baby's sleep and the type of help they would be likely to use. This study aimed to describe and identify, among mothers of a 0‐ to 24‐month‐old child, the perceived impact of lack of sleep, sleep‐related help‐seeking behaviors as well as the most concerning aspects of the child's slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…General Internet searches were the most used resource by parents and this reflects the trend of parents' increasing use of online resources to seek information about child sleep (Allen & Rainie, 2002 ; Khoo et al, 2008 ). Online delivery has been shown to be successful for the delivery of interventions for paediatric sleep (Mindell et al, 2011a ; Mindell et al, 2011b ) and recent evidence suggests that parents regularly use websites which they perceive to be reliable for child sleep (Simard & Pilon, 2021 ). Sleep specialists have begun to develop evidence‐based online content delivered in a user‐friendly fashion that includes information, advice and resources about child sleep for parents and HCPs (see Mindell et al, 2021 for an example of babysleep.com .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…General Internet searches were the most used resource by parents and this reflects the trend of parents' increasing use of online resources to seek information about child sleep (Allen & Rainie, 2002 ; Khoo et al, 2008 ). Online delivery has been shown to be successful for the delivery of interventions for paediatric sleep (Mindell et al, 2011a ; Mindell et al, 2011b ) and recent evidence suggests that parents regularly use websites which they perceive to be reliable for child sleep (Simard & Pilon, 2021 ). Sleep specialists have begun to develop evidence‐based online content delivered in a user‐friendly fashion that includes information, advice and resources about child sleep for parents and HCPs (see Mindell et al, 2021 for an example of babysleep.com .…”
Section: Discussionmentioning
confidence: 99%
“…This is of note, given that CSPs can be associated with adverse outcomes for the functioning and well‐being of both the child (Magee & Hale, 2012 ; Scher et al, 2010 ; Sivertsen et al, 2015 ; Spruyt et al, 2008 ) and family (Bayer et al, 2007 ; Martin et al, 2007 ). Parents appear particularly concerned with aspects of a child crying associated with sleep, naps, and night wakings (Simard & Pilon, 2021 ). There are multiple informal and formal healthcare resources available to parents that offer information, advice and/or help for child sleep.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…New parents experience frequent sleep disruptions due to nighttime care for their infant. Sleep changes across the first postpartum year can have a negative impact on mood, relationships, and quality of life (Da Costa et al, 2021; Medina et al, 2009; Simard et al, 2021). Studies of parents of infants and toddlers have also identified that the quality of the child’s sleep predicts parent’s sleep quality (Meltzer & Mindell, 2007; Sinai & Tikotzky, 2012).…”
Section: Introductionmentioning
confidence: 99%